Mitigating adverse effects of ettringite in mineral binder compositions
By using polymer P in the mineral binder composition, the negative impact of rapid formation of ettringite on the effectiveness of dispersant is solved, the processability of the mineral binder composition is improved and the stability of the hardening process is maintained.
Patent Information
- Application Number
- CN202380067396.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-28
- Filing Date
- 2023-09-25
- Publication Date
- 2025-04-25
AI Technical Summary
The negative effect of the rapid formation of ettringite in mineral binder compositions on the effectiveness of dispersant, resulting in an extended hardening time of the mineral binder composition and the effectiveness of the dispersant is inhibited.
Using polymer P, the polymer comprises at least one monomer unit M1 of formula I:CH2=CHNRCOR', wherein R and R' can form alkylene chains to provide a cyclic structure for improving the effectiveness of dispersants in the mineral binder composition containing ettringite.
By reducing or inhibiting the adverse effect of ettringite on the effectiveness of dispersant, polymer P significantly improves the processability of the mineral binder composition, maintaining the hydration time and stability of the hardening process of the mineral binder composition.
Smart Images

Figure BDA0005319934380000071 
Figure BDA0005319934380000101 
Figure BDA0005319934380000102
Abstract
Description
Technical Field
[0001] The present invention relates to the use of polymers for improving the effectiveness of dispersants, in particular dispersants based on polycarboxylic acid ethers, in mineral binder compositions forming and / or containing ettringite and / or for reducing or inhibiting the adverse effects of ettringite on the effectiveness of dispersants in mineral binder compositions. Background Art
[0002] Dispersants or superplasticizers are used in the construction industry as plasticizers or water reducers for mineral binder compositions, such as concrete, cement mortar, plaster or lime mortar. Dispersants are usually organic polymers, which are added to the mixing water or mixed with the binder composition in solid form. In this way, the consistency of the binder composition during processing and the properties in the hardened state can be advantageously changed.
[0003] Known particularly effective dispersants are, for example, polymers based on polycarboxylic acid ethers (PCEs). Polymers of this type have a polymer backbone and side chains bonded thereto. Corresponding polymers are described, for example, in EP 1 138 697 A1 (Sika AG).
[0004] Furthermore, EP 0 757 998 A2 (Showa Denko Kabashiki Kaisha) describes water-soluble polymers based on N-vinylcarboxylic acid amides for providing fresh mortar compositions with high flowability as well as self-compactability and resistance to segregation. These polymers can also be used together with water reducers.
[0005] However, the effectiveness of the dispersant depends on the nature of the dispersant as well as the specific components of the mineral binder composition. For example, the presence of certain contaminants such as expanded clays, even in very low amounts, may affect the effectiveness of PCE-based mixes in mortar or concrete production.
[0006] Furthermore, the composition and hydration kinetics of the mineral binder may influence the effectiveness of the dispersant. For example, the aluminate reaction, in particular the formation of ettringite, is very important with regard to the processability of cement-based materials. In particular, it is known that too rapid ettringite formation has a negative impact on the rheology of the mineral binder composition and the effectiveness of the dispersant.
[0007] To overcome this problem, hydration control chemicals are used, such as retarders. These are, for example, carboxylic acids, sugars, phosphonates, etc. EP 3 468 936 B1 (BASF SE) describes, for example, the use of special acid compounds in combination with organic carbonates for retarding the hydration reaction of the aluminate-containing clinker phase. This avoids too rapid setting of mortar and concrete slurries and ensures sufficient open time, which allows the slurry to be processed as required.
[0008] However, hydration control chemicals generally affect the hydration reaction as a whole. This results in a significant slowing down of the hardening of the mineral binder composition. For certain applications, this is undesirable.
[0009] Therefore, there is a need to develop new and improved solutions that reduce or overcome the above-mentioned disadvantages. SUMMARY OF THE INVENTION
[0011] An object of the present invention is to provide substances and methods that allow to reduce or prevent the problem of aluminate reaction, especially ettringite formation, in mineral binder compositions. Ideally, the solution should reduce the negative impact of rapid ettringite formation on the effectiveness of dispersants, especially polycarboxylate-based dispersants. Therefore, preferably, the hydration or hardening time of the mineral binder composition should be affected as little as possible. In particular, the substance or method should be compatible with conventional additives for producing mineral binder compositions or with corresponding methods. In particular, these substances or methods should be compatible with lignin sulfonates, gluconates, naphthalene sulfonates, sulfonated naphthalene-formaldehyde condensates, melamine sulfonates, vinyl copolymers, sulfonated vinyl copolymers and / or polycarboxylates, especially polycarboxylate ethers. In particular, these substances or methods should be compatible with PCE-based dispersants.
[0012] Surprisingly, it has been found that the object of the invention can be achieved by the features of claim 1. The core of the invention is therefore the use of a polymer P for improving the effectiveness of a dispersant, in particular a dispersant based on a polycarboxylic acid ether, in a mineral binder composition forming and / or containing ettringite and / or for reducing or suppressing the adverse effects of ettringite on the effectiveness of a dispersant in a mineral binder composition, the polymer P comprising:
[0013] a) at least one monomer unit M1 of formula I:
[0014] CH2=CHNRCOR'(I)
[0015] wherein R and R' are independently a hydrogen atom or a methyl group, or wherein R and R' together form an alkylene chain so as to provide, together with the N atom and the C atom to which they are attached, a cyclic structure, in particular a five-membered ring;
[0016] b) optionally at least one further monomer unit M2.
[0017] As has been shown, the polymers P of the invention allow a significant improvement in the effectiveness of dispersants, in particular dispersants based on polycarboxylic acid ethers, in mineral binder compositions forming and / or containing ettringite, and / or a reduction or suppression of the adverse effects of ettringite on the effectiveness of dispersants in mineral binder compositions.
[0018] Without wishing to be bound by theory, it is believed that polymer P is more easily adsorbed on ettringite than dispersants (e.g. polycarboxylate ether based dispersants). Therefore, when using polymer P of the present invention, the adsorption capacity of ettringite for dispersants can be reduced or eliminated. Polymer P may also act as a co-surfactant for the dispersant, shielding the latter from the effects of ettringite. The precise mechanism may depend on the nature of the mineral binder composition and the specific nature of the polymer P used. However, whatever the mechanism, the effectiveness of the dispersant is less or not affected at all by ettringite.
[0019] The solution of the invention proves to be highly robust and the polymer P has only a small influence or no influence on the hydration of the mineral binder composition. In particular, the polymer P hardly influences the hardening process of the mineral binder composition.
[0020] In addition, the polymer P of the present invention itself hardly affects the slump flow of the mineral binder composition. Therefore, the dosage of the dispersant can be kept within a certain range. This in turn reduces the need for additional adjustments to the formulation of the mineral binder composition.
[0021] Furthermore, the polymer P is well compatible with conventional additives for producing mineral binder compositions or corresponding processes, respectively. Conventional additives include, for example, dispersants, accelerators, retarders, shrinkage reducers and / or processing chemicals typically used in mortar and concrete compositions.
[0022] In particular, it is compatible with dispersants selected from the group consisting of lignin sulfonates, gluconates, naphthalene sulfonates, sulfonated naphthalene-formaldehyde condensates, melamine sulfonates, vinyl copolymers, sulfonated vinyl copolymers and polycarboxylate ethers. Among them, polycarboxylate ethers are of the greatest interest because they generally have a very pronounced dispersing effect.
[0023] Further aspects of the invention are the subject matter of further independent claims. Particularly preferred embodiments of the invention are the subject matter of the dependent claims.
[0024] Mode for carrying out the invention
[0025] A first aspect of the present invention relates to the use of a polymer P for improving the effectiveness of a dispersant, in particular a dispersant based on a polycarboxylate ether, in a mineral binder composition forming and / or comprising ettringite, and / or for reducing or inhibiting the adverse effects of ettringite on the effectiveness of a dispersant in a mineral binder composition, the polymer P comprising:
[0026] a) at least one monomer unit M1 of formula I:
[0027] CH2=CHNRCOR'(I)
[0028] wherein R and R' are independently a hydrogen atom or a methyl group, or wherein R and R' together form an alkylene chain to provide, together with the N atom and the C atom to which they are attached, a cyclic structure, in particular a five-membered ring;
[0029] b) optionally at least one further monomer unit M2.
[0030] According to the invention, the polymers P are used in particular for inertizing ettringite against the adsorption of dispersants, in particular dispersants based on polycarboxylic acid ethers.
[0031] In the context of the present invention, a "polymer" is a substance which comprises or consists of at least 2, in particular at least 3, preferably at least 5 polymerized monomer units.
[0032] In particular, the polymer P is used to improve the effectiveness of a dispersant, in particular a polycarboxylate-based dispersant, in a mineral binder composition that forms and / or contains ettringite, and / or to reduce or inhibit the adverse effects of ettringite on the effectiveness of a dispersant in a mineral binder composition, within 1 hour, in particular 30 minutes, in particular 10 minutes after mixing the mineral binder composition with water. In these time periods, early C3A-CaSO4 hydration occurs, which is most critical for the rapid formation of ettringite.
[0033] The term "effectiveness of a dispersant" relates to the ability of a dispersant, especially a polycarboxylate-based dispersant, to improve the processability of a mineral binder composition. Improved processability is increased processability. In particular, the improvement in processability can be measured as an increase in the flow table spread according to standard EN 1015-3:2007, for example directly after mixing and / or after a given time such as 5, 30, 60, 90 and 120 minutes after mixing. Higher flow table spread corresponds to improved processability. Therefore, improvements can be measured relative to the flow table spread of the same mineral binder composition that does not contain a dispersant. An effective dispersant has a very high ability to improve processability.
[0034] In other words, the present invention relates to the use of a polymer P as defined above for improving the processability of a mineral binder composition comprising a dispersant, in particular a dispersant based on a polycarboxylate ether, which forms and / or comprises ettringite, and / or for reducing or suppressing the adverse effects of ettringite on the processability of a mineral binder composition comprising a dispersant, in particular a dispersant based on a polycarboxylate ether.
[0035] "Improving the effectiveness of a dispersant" means in particular increasing the processability of a mineral binder composition comprising a dispersant, in particular increasing the flow table spread, in particular immediately after mixing the mineral binder composition with water. The improvement can be measured on the processability, in particular the flow table spread, of the same mineral binder composition comprising a dispersant but not comprising the polymer P according to the invention. In the context of the present invention, the flow table spread can be measured according to standard EN 1015-3:2007.
[0036] The "adverse effect of ettringite on the effectiveness of the dispersant" is in particular a loss of fluidity and spread of the mineral binder composition, especially immediately after the mineral binder composition is mixed with water.
[0037] As a reference for determining effectiveness and / or adverse effects, a mineral binder composition can be used which does not contain the polymer P according to the invention but which otherwise has the same composition as the mineral binder composition for use according to the invention.
[0038] The present invention also relates to a method for improving the processability of a mineral binder composition which forms and / or comprises ettringite and further comprises a dispersant, in particular a dispersant based on a polycarboxylate ether, comprising the following steps:
[0039] (i) providing a mineral binder composition,
[0040] (ii) adding a polymer to the mineral binder composition, the polymer P comprising:
[0041] a) at least one monomer unit M1 of formula I:
[0042] CH2=CHNRCOR'(I)
[0043] wherein R and R' are independently a hydrogen atom or a methyl group, or wherein R and R' together form an alkylene chain so as to provide, together with the N atom and the C atom to which they are attached, a cyclic structure, in particular a five-membered ring,
[0044] b) optionally at least one further monomer unit M2.
[0045] If R and R' together form an alkylene chain, the alkylene chain is preferably an alkylene chain having at least 3 methylene groups, in particular exactly 3 methylene groups. In other words, in the latter case, R and R' together represent a -CH2-CH2-CH2-group, or the monomer unit M1 is N-vinyl-2-pyrrolidone.
[0046] With regard to the structure of the polymer P, the monomer units M1 are preferably selected from N-vinylformamide, N-vinylacetamide, N-methyl-N-vinylformamide, N-vinyl-2-pyrrolidone and / or N-methyl-N-vinylacetamide.
[0047] With particular preference, the monomer unit M1 comprises N-vinylformamide or consists of N-vinylformamide.
[0048] In a further particularly preferred embodiment, the monomer unit M1 comprises or consists of N-vinyl-2-pyrrolidone.
[0049] According to a highly preferred embodiment, the polymer P is a homopolymer of the monomer units M1, in particular a homopolymer of N-vinylformamide or a homopolymer of N-vinyl-2-pyrrolidone.
[0050] Homopolymers have proven to be particularly advantageous for achieving the advantages of the present invention while being easy to produce.
[0051] In a further preferred embodiment, however, the polymer P is a copolymer of at least one monomer unit M1 of the formula I, in particular N-vinylformamide, and at least one further monomer unit M2.
[0052] In particular, the at least one further monomer unit M2 is different from the monomer unit M1.
[0053] The at least one further monomer unit M2 is in particular selected from vinyl-based monomers, allyl-based monomers, methallyl-based monomers, acryl-based monomers, methacryl-based monomers, isoprenolether-based monomers.
[0054] Using further monomers M2, the properties of the polymer P can be further adjusted to meet specific requirements in the mineral binder composition.
[0055] Particularly preferably, the at least one further monomer unit M2 is selected from vinyl acrylic acid, methacrylic acid, acrylamide, vinylamine, vinyl alcohol, vinyl polyalkylene glycol, allyl polyalkylene glycol, methallyl polyalkylene glycol, isoprene alcohol ether polyalkylene glycol, polyalkylene glycol acrylate and / or polyalkylene glycol methacrylate.
[0056] In particular, the at least one additional monomer unit M2 comprises the structure of formula II:
[0057]
[0058] in
[0059] R 1 and R2 is independently H or an alkyl group having 1 to 5 carbon atoms,
[0060] R 3 is independently in each case H, an alkyl group having 1 to 5 carbon atoms, preferably H or CH3 or a mixture thereof, or a group of the formula: -(CH2) m -[C=O] p -XR 4 ,
[0061] m = 0, 1 or 2,
[0062] p = 0 or 1,
[0063] X is independently at each occurrence -O-, -NH- or -O-(CH2)4-O-,
[0064] R 4 It is -[AO] n -R a Group
[0065] Where A=C2- to C4-alkylene, R a H, C1-C 20 -alkyl, -cycloalkyl or -alkylaryl,
[0066] And n=2-250, especially 10-200.
[0067] More specifically, R 1 =H or CH3 and R 2 =R 3 =H.
[0068] Advantageously at least 75 mol %, in particular at least 90 mol %, especially at least 95 mol % or at least 99 mol % of the X groups in the monomer units M2, based on the total number of monomer units M2, are -O- (=oxygen atoms).
[0069] In a further advantageous embodiment, m=0, p=1 and preferably X=—O—. In this case, the copolymers can be prepared based on commercially available (meth)acrylates.
[0070] In a further advantageous embodiment, m=0-2, p=0 and preferably X=-0-.Thus, copolymers can be prepared based on commercially available vinyl ether, (meth)allyl ether or prenyl ether monomers.
[0071] In a particularly advantageous embodiment, R 1 It is a mixture of 40-60 mol% H and 40-60 mol% -CH3.
[0072] Based on the monomer unit R 4 The total number of parts, R in the monomer unit M2 with a side chain 4 The fraction consists in particular of poly(ethylene oxide), especially to an extent of at least 50 mol %, in particular at least 75 mol %, preferably at least 95 mol % or at least 99 mol %.
[0073] The proportion of ethylene oxide units, based on the total number of alkylene oxide units in the copolymer, is in particular greater than 75 mol %, in particular greater than 90 mol %, preferably greater than 95 mol % and in particular 100 mol %.
[0074] More specifically, R 4 There are essentially no hydrophobic groups, in particular no oxyalkylene groups having three or more carbon atoms. This means in particular that the proportion of oxyalkylene groups having three or more carbon atoms is less than 5 mol %, in particular less than 2 mol %, preferably less than 1 mol % or less than 0.1 mol %, based on the total number of oxyalkylene groups. In particular, there are no oxyalkylene groups having three or more carbon atoms, i.e. their proportion is 0 mol %.
[0075] R a Advantageously, A is H and / or methyl. Particularly advantageously, A=C2-alkylene, R a It is H or methyl.
[0076] More particularly, n=10-150, especially n=15-100, preferably n=17-70, in particular n=19-45 or n=20-25.
[0077] In particular, the polymer P does not contain monomer units containing sulfonic acid groups and / or salts thereof. In particular, the polymer P does not contain monomers having the following structure: CH2=CHR 11 X 11 R 12 SO3X 12 , where R 11 =H or methyl; X 11 =CONH or COO; R 12 = a straight or branched alkylene group having 1 to 4 carbon atoms, and X 12 = Hydrogen, alkali metal, ammonium salt or organic ammonium salt.
[0078] The weight average molecular weight (M w ) is preferably 500-60000 g / mol, especially 1000-50000 g / mol, and particularly 2000-15000 g / mol. The weight average molecular weight (M W ) were determined by gel permeation chromatography (GPC) using polyethylene glycol (PEG) as a standard.
[0079] In particular, the polymer P comprises or consists of, relative to the total number of monomer units present in the polymer P:
[0080] a) 30 to 100 mol %, in particular 50 to 100 mol %, in particular 60 to 100 mol %, preferably 75 to 100 mol %, more preferably 80 to 100 mol %, still more preferably 90 to 100 mol % or 98 to 100 mol % of monomer units M1 of the formula I, in particular N-vinylformamide and / or N-vinyl-2-pyrrolidone;
[0081] b) optionally 0.1 to 70 mol %, especially 1 to 50 mol %, in particular 5 to 40 mol %, preferably 10 to 25 mol %, of at least one further monomer unit M2.
[0082] In particular, the molar proportion of monomer units M1 of formula I, in particular N-vinylformamide, is higher than the molar proportion of at least one further monomer unit M2, in particular, the molar proportion of monomer units M1 of formula I is at least equal to 1.1 times, in particular at least 1.5 times, in particular 2 times, for example at least 5 times the molar proportion of at least one further monomer unit M2.
[0083] In particular, the molar ratio of monomer unit M1 of formula I, especially N-vinylformamide, to at least one further monomer unit M2 is preferably 1:1-100:1, preferably 1:1-90:1, more preferably 1:1-75:1, especially 1.1:1-50:1, in particular 1.5:1-25:1.
[0084] The polymers are prepared in particular by free-radical polymerization, for example by conventional free-radical polymerization or by controlled free-radical polymerization (also called living free-radical polymerization). These polymerization techniques are well known to those skilled in the art.
[0085] In particular, the polymer P is used in liquid or solid form.
[0086] For example, the polymer P can be provided in the form of a liquid admixture, in particular dissolved or dispersed in a solvent, such as water.
[0087] Furthermore, the polymer P can be provided in the form of a solid admixture, for example in the form of a powder, optionally together with further powders, for example carrier materials and / or filler materials.
[0088] The polymer P is preferably used in a proportion of 0.0001-10% by weight, especially 0.001-5% by weight, particularly 0.005-2% by weight, in particular 0.01-0.2% by weight, for example 0.01-0.1% by weight, relative to the total weight of the mineral binder in the mineral binder composition. With these proportions, the reduction of the adverse effects of ettringite and / or the improvement of the effectiveness of the dispersant is optimal and at the same time the hydration of the mineral binder composition with water is as small as possible.
[0089] The polymer P is preferably used in combination with a polycarboxylate ether dispersant.
[0090] The proportion of the polycarboxylate ether dispersant, relative to the total weight of the mineral binder in the mineral binder composition, is in particular 0.0001-10% by weight, in particular 0.001-5% by weight, in particular 0.01-2% by weight, in particular 0.01-0.5% by weight.
[0091] The weight ratio of polymer P to polycarboxylate ether dispersant is in particular from 0.01 to 2, in particular from 0.1 to 1, in particular from 0.2 to 0.8, for example from 0.4 to 0.7.
[0092] The polycarboxylate ether is preferably a comb polymer CP having the following substructure units:
[0093] a) a molar parts of substructure unit S1 of formula III:
[0094]
[0095] b) b molar parts of substructure unit S2 of formula IV
[0096]
[0097] c) c molar parts of substructure unit S3 of formula (V):
[0098]
[0099] d) d molar parts of substructure unit S4 of formula (VI)
[0100]
[0101] in
[0102] L independently represents H + , alkali metal ions, alkaline earth metal ions, divalent or trivalent metal ions, ammonium ions or organic ammonium groups,
[0103] Each R u are independently hydrogen or methyl,
[0104] Each R vindependently of each other are hydrogen or COOM,
[0105] r = 0, 1 or 2,
[0106] t = 0 or 1,
[0107] G 1 and G 2 Independently C1-C 20 -alkyl, -cycloalkyl, -alkylaryl or -(CH2) z -(O) z’ -[A'O] s -G 4 ,
[0108] wherein z=0, 1, 2, 3 or 4, z'=0 or 1, A'=C2- to C4-alkylene, G 4 Yes H, C1-C 20 -alkyl, -cycloalkyl or -alkylaryl, and s=2-250,
[0109] G 3 Independently NH2, -NG 5 G 6 , -OG 7 NG 8 G 9 ,
[0110] Among them G 5 and G 6 Independently
[0111] C1-C 20 -alkyl, -cycloalkyl, -alkylaryl or -aryl,
[0112] or hydroxyalkyl or acetoxyethyl (CH3-CO-O-CH2-CH2-) or hydroxyisopropyl (HO-CH(CH3)-CH2-) or acetoxyisopropyl (CH3-
[0113] CO-O-CH(CH3)-CH2-);
[0114] or G 5 and G 6 together to form a ring of which the nitrogen is a part to construct a morpholine or imidazoline ring;
[0115] G 7 is C2-C4 alkylene,
[0116] G 8 and G 9 Each independently represents C1-C 20 -alkyl, -cycloalkyl, -alkaryl, -aryl or hydroxyalkyl,
[0117] and wherein a, b, c and d represent the molar ratio of the corresponding substructure units S1, S2, S3 and S4, wherein
[0118] a / b / c / d=(0.1-0.9) / (0.1-0.9) / (0-0.8) / (0-0.8),
[0119] In particular, a / b / c / d = (0.3-0.9) / (0.1-0.7) / (0-0.6) / (0-0.4),
[0120] Preferably a / b / c / d=(0.5-0.8) / (0.2-0.4) / 0 / 0
[0121] And the condition is a+b+c+d=1.
[0122] A "comb polymer" is a polymer comprising a polymer backbone and side chains bonded thereto.
[0123] The order of the substructure units S1, S2, S3 and S4 can be alternating, block-wise or random. One or more substructure units S1, S2, S3 and S4 can also form a gradient structure. In principle, other structural units can also be present in addition to the substructure units S1, S2, S3 and S4. In particular, the order of the substructure units S1, S2, S3 and S4 in the comb polymer CP is random or statistical.
[0124] Preferably, the substructure units S1, S2, S3 and S4 together have a proportion of at least 50% by weight, in particular at least 90% by weight, most preferably at least 95% by weight, of the total weight of the comb polymer CP.
[0125] In comb polymers CP, R v In particular, it represents hydrogen and R u Preferred are hydrogen and / or methyl.
[0126] Preferably, in the comb polymer CP, r = 0 and t = 1. Likewise advantageously, r = 1-2 and t = 0.
[0127] More specifically, in the comb polymer CP, R v is hydrogen, R u is methyl, r=1-2 and t=0.
[0128] G in comb polymer CP 1 and / or G 2 Advantageously, in each case independently -[A'O] s -G 4 , wherein s=8-200, especially 20-70, and A' is C2- to C4-alkylene. Thus, advantageously z=z'=0.
[0129] In the comb polymer CP, G 4 Preferred independently at each occurrence is hydrogen or methyl.
[0130] Very particularly advantageous comb polymers CP are those in which
[0131] a) R u and R v Part of it is hydrogen,
[0132] b) r = 0,
[0133] c) t=1,
[0134] d) G 1 and G 2 is independently in each case -(CH2) z -(O) z’ -[A'O] s -G 4 , where z = z' = 0, s = 20-70, and
[0135] A'=C2-alkylene,
[0136] e)G 4 represents methyl and / or
[0137] f) a / b / c / d=(0.5-0.8) / (0.2-0.4) / (0.001-0.005) / 0 Likewise advantageous polymers CP are those wherein
[0138] a) t = 0 and r = 1-2,
[0139] b) G 1 is independently in each case -(CH2) z -(O) z’ -[A'O] s -G 4 , wherein z=z'=0, s=8-200, especially 20-70,
[0140] c) G 4 means hydrogen or methyl, especially hydrogen,
[0141] d) and / or A' is C2- to C4-alkylene, especially C2-alkylene.
[0142] The weight average molecular weight (M) of polymer CP W ) is particularly in the range of 5000-150000 g / mol, preferably 10000-100000 g / mol, especially 20000-90000 g / mol. W) was determined by gel permeation chromatography (GPC) using polyethylene glycol (PEG) as a standard.
[0143] The preparation of comb polymers CP is known per se to the person skilled in the art. Corresponding superplasticizers or comb polymers CP are also available from Sika Schweiz AG as Trade name series commercially available.
[0144] The term "mineral binder" means a binder which reacts in a hydration reaction in the presence of water to form a solid hydrate or a hydrate phase. This can be, for example, a hydraulic binder, a latent hydraulic binder and / or a pozzolanic binder. Highly preferred are hydraulic binders. Hydraulic binders can solidify underwater. However, it is advantageous for the mineral binder to contain other binders in addition to or instead of the hydraulic binder. These are in particular latent hydraulic binders and / or pozzolanic binders. Suitable latent hydraulic and / or pozzolanic binders are, for example, slag, fly ash, silica powder and / or natural pozzolanic ash. The mineral binder in the mineral binder composition contains substances which are able to form ettringite during the hydration of the mineral binder composition.
[0145] In particular, the mineral binder in the mineral binder composition comprises an aluminate-containing phase and calcium sulfate. The aluminate-containing phase is, for example, tricalcium aluminate (C3A), monocalcium aluminate (CA), tetraaluminate ferrate (C4AF), dodecaluminate heptaaluminate (C4AF), calcium sulfate ... 12 A7) and / or calcium sulphoaluminate (yeelimite) (C4A3$).
[0146] In particular, the mineral binder comprises tricalcium aluminate and calcium sulfate. According to an embodiment, the mineral binder comprises 0.1-10w%, preferably 0.5-8w%, more preferably 1-7w% of tricalcium aluminate based on the total dry weight of the mineral binder. According to an embodiment, the mineral binder comprises 0.1-5w%, preferably 0.5-3w% of calcium sulfate based on the total dry weight of the mineral binder.
[0147] After adding mixing water to the mineral binder, the aluminate-containing phases such as tricalcium aluminate and calcium sulfate will form ettringite in a hydration reaction. ettringite is a hydrous calcium aluminum sulfate mineral. ettringite can be represented by the following formula: Ca6Al2(SO4)3(OH) 12 ·26H2O.
[0148] In particular, the mineral binder comprises cement or consists of cement, in particular CEM I, CEM II, CEM II I, CEM V and / or CEM V cement (according to standard EN 197-1). These types of cement may contain tricalcium aluminate (C3A) and calcium sulfate in proportions of up to 5% by weight as secondary components. Therefore, ettringite formation usually occurs in such cements.
[0149] According to an embodiment, the mineral binder forms at least 0.1 wt. %, preferably at least 0.2 wt. % ettringite relative to the total dry weight of the cured mineral binder. The amount of ettringite can be determined by TGA analysis as described in the Examples section.
[0150] In a preferred embodiment, the mineral binder contains at least 5% by weight, in particular at least 20% by weight, preferably at least 35% by weight, in particular at least 65% by weight, of hydraulic binder, in particular cement, and optionally 5 to 95% by weight, in particular 5 to 65% by weight, in particular 15 to 35% by weight, of latent hydraulic and / or pozzolanic binders, relative to the total mineral binder content.
[0151] According to an embodiment, the mineral binder comprises clay (C), in particular calcined clay, limestone (LS) and Portland cement (PC) in the following weight ratios:
[0152] - PC:C is 33:1 to 1:1, preferably 8:1 to 1:1,
[0153] - C:LS is 10:1 to 1:50, preferably 10:1 to 1:33, more preferably 5:1 to 1:10, and
[0154] - PC:LS is 20:1 to 1:4, preferably 5:1 to 1:1.
[0155] Clay in the context of the present invention is a solid material, each of which, relative to its dry weight, consists of at least 30w%, preferably at least 35w%, and in particular at least 75w% of clay minerals. Such clay minerals preferably belong to the kaolin group (e.g. kaolinite, dickite, nacrite or halloysite), smectite group (e.g. montmorillonite, nontronite or saponite), vermiculite group, serpentine, palygorskite, sepiolite, chlorite, talc, pyrophyllite, mica (e.g. biotite, muscovite, illite, glauconite, green phosphorite and moonstone) or mixtures thereof. Clay minerals belonging to the kaolin group are particularly preferred, especially kaolinite and mica, especially muscovite and illite, and mixtures thereof. Clay minerals in the context of the present invention may be any type of clay mineral, such as crude clay, low-temperature calcined clay or high-temperature calcined clay. Crude clay is a clay mineral extracted, for example, from a quarry, optionally purified and optionally dried. Low temperature calcined clay is clay that has been heat treated at a temperature of 500-1200°C. This low temperature calcination generally results in the removal of interlayer water and at least partial, preferably complete, dehydroxylation. For example, low temperature calcined clay minerals can be produced in a rotary kiln or a flash calciner. High temperature calcined clay is clay mineral that has been heat treated at a temperature above 1200°C and generally between 1300-1400°C. High temperature calcined clay is generally crystalline or contains a large amount of crystalline phases, especially crystalline phases of mullite.
[0156] The clay in the context of the present application is preferably a low-temperature calcined clay. Low-temperature calcined clay is a clay material that has been subjected to a heat treatment, preferably at a temperature of 500-1200°C, or in a fast calcination process of 800-1100°C. Suitable fast calcination methods are described, for example, in WO 2014 / 085538. The low-temperature calcined clay is an anhydrous material. It is preferred herein that during the calcination of the clay, the clay material is dehydroxylated to an amorphous material while preventing the formation of a crystalline high-temperature aluminosilicate phase such as mullite. Low-temperature calcined clays, especially low-temperature calcined kaolinite, are generally amorphous, have a significantly higher specific surface area than the original clay, and have pozzolanic activity. According to a particularly preferred embodiment of the present invention, the calcined clay is metakaolin. Metakaolin is a material obtained by low-temperature calcination of kaolinite or a kaolinite-rich mineral, for example, with respect to its dry weight, the content of kaolinite is at least 30% by weight, preferably at least 35% by weight. The calcination temperature for producing metakaolin is usually 500-900°C.
[0157] According to an embodiment, the mineral binder consists of clay, limestone and Portland cement to an extent of at least 65% by weight, preferably at least 80% by weight, more preferably at least 92% by weight, in each case relative to the total dry weight of the mineral binder.
[0158] According to an embodiment of the invention, the mineral binder comprises a mixture of:
[0159] a) 25-100 parts by mass of Portland cement (PC),
[0160] b) 3 to 50 parts by mass of clay (C), in particular calcined clay, especially metakaolin,
[0161] c) 5-100 parts by mass of limestone (LS).
[0162] According to a further embodiment of the invention, the mineral binder comprises a mixture of:
[0163] a) 5-95w%, preferably 6-80w% of a slag-based binder, the slag-based binder comprising or consisting of:
[0164] a1) at least one ironmaking slag, preferably granulated blast furnace slag,
[0165] a2) optionally, a second slag different from a1), preferably basic oxygen furnace slag, a3) optionally latent hydraulic additives and / or pozzolanic additives, preferably silica dust, natural pozzolans, fly ash and / or burned oil shale,
[0166] b) 5-95 w%, preferably 20-94 w%, of at least one auxiliary binder which is different from the slag-based binder a) and which is selected from Portland cement, calcium aluminate cement and / or calcium sulphoaluminate cement, in particular Portland cement,
[0167] c) 0-10w% of additives, especially activators.
[0168] A "mineral binder composition" is a composition comprising a mineral binder and optionally one or more further components, in particular as described below. The mineral binder composition may be present in the form of a dry composition or in the form of a composition to be mixed with water.
[0169] Furthermore, the mineral binder composition may contain aggregates. The term "aggregate" includes any type of mortar and / or concrete aggregate. In particular, the aggregate is characterized by a density of 2.2-3 kg / dm 3 .
[0170] In particular, the aggregate comprises stone, gravel, sand, powdered quartz and / or limestone. However, the aggregate may comprise or consist of lightweight aggregates, in particular foamed clay or polystyrene, or heavy aggregates, such as barite, iron ore, etc.
[0171] In particular, the aggregate has a particle size of at least 0.125 mm or at least 0.250 mm, preferably, the aggregate has a particle size of at most 125 mm or at most 32 mm. In particular, the aggregate has a particle size of 0.125-125 mm, especially 0.125-32 mm, in particular 0.125-16 mm, for example 0.125-8 mm or 0.125-5 mm.
[0172] In this context, particle size is determined by sieve analysis, in particular using a sieve with square openings. In particular, particle size is expressed as the size of the opening of the test sieve just passed by the relevant particle or particles.
[0173] Furthermore, the mineral binder composition may contain additives, in particular selected from additives commonly used in mortar or concrete compositions. In particular, the additives are selected from plasticizers, accelerators; corrosion inhibitors; retarders; shrinkage reducers; defoamers and / or foaming agents. Thus, the additives are chemically and / or physically different from the dispersant and the polymer P.
[0174] The proportion of additives is in particular 0.0001-10% by weight, especially 0.001-5% by weight, in particular 0.01-2% by weight, relative to the total weight of the mineral binder in the mineral binder composition.
[0175] In particular, the mineral binder composition is a grout, mortar or concrete composition.
[0176] To prepare the mineral binder composition, mixing water is added.
[0177] Preferably, the ratio of water to mineral binder in the mineral binder composition is in particular 0.25-0.8, especially 0.3-0.6, for example 0.4-0.5.
[0178] In particular, the polymer P is added to the mineral binder composition before the mixing water is added to the mineral binder composition. Therefore, the polymer P is preferably uniformly mixed with the other components of the mineral binder composition. In this case, for example, the polymer P can be added in the form of a solid or liquid mixture as described above.
[0179] This ensures that the polymer P is present in the mineral binder composition when the hydration reaction and the formation of ettringite are initiated.
[0180] In particular, the polymer P is added to the mineral binder composition before the addition of the dispersant.
[0181] In particular, the polymer P is added to the mineral binder during its production, for example in a cement mill, in particular by grinding the polymer P with the mineral binder. The proportion of polymers can thereby be adjusted depending on the properties of the mineral binder, for example the proportion of sulfate and / or aluminate phases in the mineral binder.
[0182] In particular, the polymer P can be provided as an admixture comprising the polymer P, the dispersant and optionally further additives. This simplifies the use of the polymer P, since the ratio can be fixed.
[0183] However, the polymer P can be added independently of the other additives or components of the mineral binder composition. This is the most flexible, since the proportion of polymer P can be adjusted as required independently of the other components or additives. Thus, for example, the polymer P can be added together with the dispersant and / or after the dispersant.
[0184] Another aspect of the invention relates to a mineral binder or a mineral binder composition comprising a polymer P and a dispersant as described above. In particular, the mineral binder and the mineral binder composition are defined as described above. In particular, the mineral binder or the mineral binder composition comprises substances capable of forming ettringite during hydration of the mineral binder composition, in particular tricalcium aluminate (C3A) and calcium sulfate.
[0185] According to a particular embodiment, the mineral binder composition comprising a mineral binder, a polymer P and water has a content of dissolved aluminate and dissolved sulfate. In particular, the content of dissolved aluminate and dissolved sulfate is such that the molar ratio of aluminate:sulfate is about 2:3.
[0186] Another aspect relates to a kit of parts, which comprises a polymer P as described above and a dispersant for a mineral binder composition, in particular a polycarboxylate ether which is chemically and / or structurally different from the polymer P. In particular, the kit of parts is in the form of a one-component, two-component or multi-component admixture. In a two-component or multi-component admixture, the polymer P and the dispersant are preferably provided as spatially separated components.
[0187] Another aspect relates to a method, in particular a method for plasticizing a mineral binder composition, comprising the steps of adding to the mineral binder composition a polymer P as described above and a dispersant for a mineral binder composition as described above.
[0188] Further advantageous embodiments and combinations of features of the invention emerge from the following exemplary embodiments and from the entire patent claims.
[0189] Exemplary embodiments
[0190] Preparation of polymer P
[0191] Poly(N-vinylformamide) and polyvinylpyrrolidone were purchased and used as received.
[0192] Polymers P1 and P2 were prepared according to the following general procedure:
[0193] Comonomer 1 (type and amount as shown in Table 1 below) was added to a glass reactor with a thermometer, agitator, a dropping funnel and a reflux condenser and diluted with water to an amount equal to 3 times the initial weight of comonomer 1. The resulting mixture was heated to 80°C. During the heating period and throughout the remaining reaction time, a gentle inert gas stream (N2) was passed through the stirred solution. 3.5 wt% (based on comonomer 1) of 4-cyano-4-(thiobenzoylthio) valeric acid was added. Once the material had completely dissolved, 0.7 wt% (based on comonomer 1) of azobisisobutyronitrile was added. From then on, the conversion was regularly determined by HPLC. Once the conversion (based on comonomer 1) exceeded 85%, comonomer 2 was added to the reaction mixture. After 2.5 hours, all comonomer 2 had reacted according to HPLC measurement. A polymer with a block distribution of monomer units was obtained. A slightly reddish polymer solution was obtained.
[0194] Polymers P3, P4 and P5 were prepared according to the following general procedure:
[0195] Comonomer 1 (type and amount as shown in Table 1 below) and water in an amount equal to the initial weight of comonomer 1 were added to a glass reactor with a thermometer, a stirrer, a dropping funnel and a reflux condenser. 0.8 wt % of a 10% aqueous solution of Fe(II)SO4*7H2O and 0.8 wt % of sodium hypophosphite (each based on comonomer 1) were added. Subsequently, at a temperature of 25-50° C., 1.3 wt % (based on comonomer 1) of a 35% aqueous solution of hydrogen peroxide, each type and amount of comonomer 2 and optional comonomer 3, and 0.7 wt % (based on comonomer 1) of a 5% aqueous solution of initiator sodium hydroxymethylsulfinate were added dropwise over 15 minutes by a separate feed under stirring. The reaction solution was cooled to avoid a temperature increase above 50° C. The reaction mixture was then further stirred until peroxide was no longer detected. A polymer having a random distribution of monomer units was obtained. Each polymer was obtained as an aqueous solution.
[0196] Table 1: Prepared polymers
[0197]
[0198] PEGMA: Polyethylene glycol monomethacrylate (M W =1000g / mol)
[0199] HPEG: methallyl alcohol initiated polyethylene glycol (M w =2400 g / mol)
[0200] VP: Vinyl pyrrolidone
[0201] VF: Vinyl formamide
[0202] Mortar mixture
[0203] The efficacy of the polymer P according to the invention was tested in different mortar compositions.
[0204] The first mortar mix MH is based on a mineral binder that forms a large amount of ettringite. The second mortar mix ML is based on a binder that forms a small amount of ettringite. The dry composition of the mortars is shown in Table 2.
[0205] Table 2:
[0206]
[0207] To mix the mortar mixture, binder and sand were mixed in a Hobart mixer in the dry state for 1 minute. Mixing water (225 g, w / b=0.5) was added within 30 seconds and mixed for a further 2.5 minutes. The total wet mixing time was 3 minutes in each case.
[0208] Depending on the specific experiment, polymer P and / or dispersant are added together with the mixing water, as shown in Tables 3 and 4.
[0209] test
[0210] In order to determine the effectiveness of the polymer P, the corresponding flow table spread (FTS) was measured according to standard EN 1015-3:2007 5, 30, 60, 90 and 120 minutes after mixing.
[0211] Furthermore, heat flow calorimetry was performed on the mortar composition samples by isothermal calorimetry at 23°C. The calorimetric curve represents the energy released in [W / g mineral binder] as a function of time [h] in the mortar mix specimen. The heat generation is due to the exothermic reaction of the silicate phase in the mineral binder with water. The maximum of the curve obtained by calorimetry can be correlated with the strength development in the cement, i.e. a maximum occurring at an earlier time means an earlier development of early strength in the component.
[0212] The formation of ettringite was measured as follows: Cement with a known C3A (tricalcium aluminate) content was mixed with water to give a water to cement weight ratio of 0.35. A high range water reducer ( Obtained from Sika Schweiz AG) with mixing water. Tests were carried out with or without the addition of polyvinyl formamide. 10 minutes after the addition of the mixing water, the hydration reaction was terminated by the addition of isopropanol and the sample was then completely dried. The dried sample was subjected to thermogravimetric analysis (TGA). The mass loss between 70-100° C. corresponds to the amount of ettringite formed.
[0213] Hereinafter, experiments R1-R7 are reference examples not according to the present invention. Experiments A1-A9 and B1-B2 are according to the present invention.
[0214] Example 1
[0215] In Example 1, various polymers P were evaluated in mortar mixes. The results of the different experiments performed are shown in Tables 3 and 4.
[0216] Table 3:
[0217]
[0218]
[0219] 1) Poly(N-vinyl formamide); % by weight relative to the binder
[0220] 2) Polyvinylpyrrolidone (M W =10'000g / mol); relative to the weight % of the binder
[0221] 3) Sika Viscocrete; Dispersant based on polycarboxylate ether; % by weight relative to binder
[0222] Experiment R1 shows that the initial flow (5 minutes after preparation) of the mortar composition without any dispersant is quite low, i.e. 146 mm, and the silicate hydration peak is around 510 minutes. When a dispersant is added without the polymer P of the present invention (see Experiment R2), the initial flow can be improved to 185 mm, while the silicate hydration peak moves to a later time.
[0223] Adding polymer P according to the invention without any dispersant (see experiment R3) did not improve the flowability of the mortar composition, while the silicate hydration peak was only slightly shifted to a later time. It can therefore be concluded that polymer P itself has no dispersing effect and hardly affects the hardening time.
[0224] However, when polymer P is used in combination with a dispersant (experiments A1-A3), the flowability is significantly improved at all times compared to reference example R2, while hardening is only very slightly delayed. It can therefore be concluded that the polymer P of the invention is indeed able to improve the effectiveness of the dispersant in a mineral binder composition forming ettringite or to reduce the adverse effects of ettringite on the effectiveness of the dispersant.
[0225] While experiments R1-R3 were all carried out with mortar mixtures MH that formed rather high amounts of ettringite, in experiment R4 a mortar mixture ML with a mineral binder containing less aluminates was used. This resulted in a much better flow, comparable to the flowability of experiment R2, even without a dispersant. However, in order to obtain these results, the entire mortar recipe needed to be changed. Thus, binders from different plants, regions, types or even between production batches may easily vary in their composition and thus result in different levels of ettringite formation. This may have an impact on the robustness of the dispersant. Therefore, the solution of the present invention has greater flexibility. In particular, it can be used to solve the problem of ettringite formation in essentially any type of mortar or concrete composition, even when the binder composition varies between different production batches from the same plant.
[0226] Table 4:
[0227]
[0228] 1) In each case 0.15 wt. % relative to the binder
[0229] 3) Sika Viscocrete; Dispersant based on polycarboxylate ether; % by weight relative to binder
[0230] Compared to R5, experiments A5 to A9 show that copolymers comprising monomer units derived from vinylpyrrolidone or N-vinylformamide do improve the fluidity of the mortar composition in the presence of a dispersant and that the silicate hydration peak is only slightly shifted to a later time.
[0231] Example 2
[0232] In Example 2, polymer P was evaluated in mixtures that formed little or much ettringite. In the experiments, two different types of cement were used. Cement A was CEM I / A-LL 42.5R with 5.70 wt% C3A and 4.5 wt% sulfate content. Cement B was CEM I 42.5R SR (sulfate resistant) with 0.60 wt% C3A and 4.40 wt% sulfate content. The test results are shown in Table 5.
[0233] Table 5
[0234]
[0235] 1) Poly(N-vinyl formamide); % by weight relative to the binder
[0236] 2) Sika Viscocrete; Dispersant based on polycarboxylate ether; % by weight relative to binder
[0237] 3) In wt %, relative to the total weight of the dry sample
[0238] Comparison of R6 and B1 shows that the addition of polymer P increases FTS in cases where significant amounts of ettringite are formed. Comparison with R7 and B2 shows that the increase in FTS is less pronounced in cases where less ettringite is formed. It can therefore be concluded that polymer P of the present invention is particularly effective in reducing or inhibiting the adverse effects of ettringite.
[0239] Those skilled in the art will appreciate that, without departing from the spirit or essential characteristics of the present invention, the present invention can be implemented in other specific forms. Therefore, the presently disclosed embodiments are considered in all aspects to be illustrative rather than restrictive.
Claims
1. Use of a polymer P for improving the effectiveness of a dispersant, in particular a dispersant based on a polycarboxylic acid ether, in a mineral binder composition forming and / or containing ettringite and / or for reducing or suppressing the adverse effects of ettringite on the effectiveness of a dispersant in a mineral binder composition, the polymer P comprising: a) at least one monomer unit M1 of formula I: CH2=CHNRCOR'(I) wherein R and R' are independently a hydrogen atom or a methyl group, or wherein R and R' together form an alkylene chain to provide, together with the N atom and the C atom to which they are attached, a cyclic structure, in particular a five-membered ring; b) optionally at least one further monomer unit M2.
2. The method according to claim 1, wherein the monomer unit M1 is N-vinylformamide and / or N-vinyl-2-pyrrolidone.
3. The method according to claim 1, wherein the polymer P is a homopolymer of N-vinylformamide or a homopolymer of N-vinyl-2-pyrrolidone.
4. The method according to claim 1, wherein the polymer P is a copolymer of at least one monomer unit M1 of formula I, in particular N-vinylformamide, and at least one other monomer unit M2.
5. The method according to claim 1, wherein the at least one additional monomer unit M2 is selected from vinyl-based monomers, allyl-based monomers, methallyl-based monomers, acryl-based monomers, methacryl-based monomers, prenol ether-based monomers.
6. The method according to claim 1 , wherein the at least one further monomer unit M2 is selected from vinyl acrylic acid, methacrylic acid, acrylamide, vinylamine, vinyl alcohol, vinyl polyalkylene glycol, allyl polyalkylene glycol, methallyl polyalkylene glycol, isoprene alcohol ether polyalkylene glycol, polyalkylene glycol acrylate and / or polyalkylene glycol methacrylate.
7. The use according to any one of the preceding claims, wherein the at least one additional monomer unit M2 comprises a structure of formula I in R 1 and R 2 is independently H or an alkyl group having 1 to 5 carbon atoms, R 3 is independently in each case H, an alkyl group having 1 to 5 carbon atoms, preferably H or CH3 or a mixture thereof, or a group of the formula: -(CH2) m -[C=O] p -XR 4 , m = 0, 1 or 2, p = 0 or 1, X is independently at each occurrence -O-, -NH- or -O-(CH2)4-O-, R 4 It is -[AO] n -R a Group Where A=C2- to C4-alkylene, R a H, C1-C 20 -alkyl, -cycloalkyl or -alkylaryl, And n=2-250, especially 10-200.
8. The use according to any one of the preceding claims, wherein the weight average molecular weight (M w ) is 500-60000 g / mol, especially 2000-50000 g / mol, especially 2000-15000 g / mol.
9. The use according to any one of the preceding claims, wherein the polymer P comprises, relative to the total number of monomer units present in the polymer P: a) 30 to 100 mol %, in particular 50 to 100 mol %, especially 60 to 100 mol %, preferably 75 to 100 mol %, more preferably 80 to 100 mol %, still more preferably 90 to 100 mol % or 98 to 100 mol % of monomer units M1 of the formula I, in particular N-vinylformamide; b) optionally 0.1 to 70 mol %, especially 1 to 50 mol %, in particular 5 to 40 mol %, preferably 10 to 25 mol %, of at least one further monomer unit M2.
10. The method according to claim 1, wherein the molar ratio of the monomer unit M1 of formula I, in particular N-vinylformamide, to the at least one further monomer unit M2 is 1:1 to 100:1, preferably 1:1 to 90:1, more preferably 1:1 to 75:1, in particular 1.1:1 to 50:1, in particular 1.5:1 to 25:
1.
11. The method according to claim 1, wherein the polymer P is used in a proportion of 0.0001-10% by weight, in particular 0.001-5% by weight, in particular 0.005-2% by weight, in particular 0.01-0.2% by weight, for example 0.01-0.1% by weight, relative to the total weight of the mineral binder in the mineral binder composition.
12. The use according to any one of the preceding claims, wherein the polymer P is used in combination with a polycarboxylate ether dispersant.
13. The use according to any of the preceding claims, wherein the polymer P is added to the mineral binder or the mineral binder composition before the mixing water is added to the mineral binder composition.
14. Use according to any one of the preceding claims, wherein the mineral binder in the mineral binder composition comprises tricalcium aluminate (C3A) and calcium sulfate.
15. A mineral binder composition comprising substances capable of forming ettringite during hydration of the mineral binder composition, in particular tricalcium aluminate (C3A) and calcium sulfate, the mineral binder composition further comprising a polymer P as defined in any one of claims 1 to 14 and optionally a polycarboxylate ether dispersant.
Citation Information
Patent Citations
Polymers for cement dispersing admixtures
EP1138697A1
Hydration control mixture for mortar and cement compositions
EP3468936B1
System for the production of fine lime
WO2014085538A1